Uji Efektivitas Antidiabetes Rebusan Daun Belimbing Wuluh (Averrhoa bilimbi L.) pada Mencit (Mus musculus) - Washliaty Sirajuddin; Shabran Hadiq; Rahmatullah Rahmatullah (Journal of Pharmaceutical and Health Research, 2023)
Diabetes mellitus is a condition where blood glucose levels increase due to the body's metaboIism of protein, fat, and carbohydrates. The purpose of this study was to determine the antidiabetic effectiveness of star fruit leaf decoction (Averrhoa bilimbi L.) on mice (Mus musculus). This type of research is a laboratory experimental study using 15 male mice divided into 5 groups of mice, each of which is fed for ± 8 hours. Then, the blood glucose level of mice was measured after being fed. Then, a glucose solution of 0.195 mg/0.2 ml was given. Next, blood glucose was measured, if each group of mice had experienced an increase in blood glucose levels, then given a negative control solution, positive control, and 10%, 15% and 20% decoction of starfruit leaves. Then measured the glucose levels of mice using a glucometer at 30, 60, and 90 minutes. The results showed that giving a 20% concentration of star fruit leaf (Averrhoa bilimbi L) decoction was effective as an antidiabetic with a percentage reduction of 42% in mice (Mus musculus).